Umpcare counselling system using ionic angular - Muhammad Umar, Ab Aziz; Junaida, Sulaiman (2021)
Counselling Unit is an organization that can provide support to the problematic student. They will guide these students to identify their problem and find a way to solve them. They have provided several types of service for the student such as deliver counselling session and career advice. P1 and P2 student is required to get consultation from the counsellor